Perlindungan Hukum Wajib Pajak Terkait Ketentuan Official Assessment-System Dalam Bidang Pajak Bumi dan Bangunan - Lisa Nadya Afifah (Jurist-Diction, 2022)
AbstractThis legal research concluded that, it is necessary to explain the concept of the official assessment-system and self-assessment-system to address the vague issue of the concept of tax collection in the Regional Tax and Retribution Law and the Cipta Kerja Law. Regarding the official-assessment system that is still used in the collection of Land and Building Tax, tax officials who have full authority in issuing tax assessments, have the potential to take actions for benefit themselves in determining the amount of tax that the taxpayer is obliged to pay. Government in terms of taxpayer losses due to the issuance of a Tax Assessment has a responsibiliy based on the concept of occupational and personal accountability in administrative law.Keywords: Tax-Collecting System; Land and Building Tax; Government Official Responsibility. AbstrakPenelitian ini membahas mengenai kekaburan konsep pemungutan pajak dalam UU Pajak Daerah dan Retribusi Daerah serta UU Cipta Kerja. Berkaitan dengan sistem official-assessment yang masih digunakan dalam pemungutan Pajak Bumi dan Bangunan, pejabat perpajakan yang memiliki wewenang penuh dalam penerbitan Surat Ketetapan Pajak, berpotensi melakukan perbuatan yang menguntungkan dirinya sendiri terkait penentuan besarnya pajak yang berkewajiban dibayar oleh Wajib Pajak. Pejabat perpajakan dalam hal kerugian Wajib Pajak akibat penerbitan Surat Ketetapan Pajak (SKP) memiliki tanggung jawab berdasarkan konsep tanggung jawab jabatan dan pribadi dalam hukum administrasi. Kata Kunci: Sistem Pemungutan Pajak; Pajak Bumi dan Bangunan; Tanggung Jawab Pejabat Pemerintahan.